FOREVER22: galaxy formation in protocluster regions. Issue 3 (27th October 2021) - Yajima, Hidenobu; Abe, Makito; Khochfar, Sadegh; Nagamine, Kentaro; Inoue, Akio K; Kodama, Tadayuki; Arata, Shohei; Dalla Vecchia, Claudio; Fukushima, Hajime; Hashimoto, Takuya; Kashikawa, Nobunari; Kubo, Mariko; et al.
ABSTRACT: We present results from a new cosmological hydrodynamics simulation campaign of protocluster (PC) regions, FOREVER22: FORmation and EVolution of galaxies in Extremely overdense Regions motivated by SSA22. The simulations cover a wide range of cosmological scales using three different zoom set-ups in a parent volume of $(714.2~\rm cMpc)^{3}$ : PCR (Proto-Cluster Region; V = (28.6 cMpc) 3, SPH particle mass, m SPH = 4.1 × 10 6  M⊙, and final redshift, z end = 2.0), BCG (Brightest proto-Cluster Galaxy; V ∼ (10 cMpc) 3, m SPH = 5.0 × 10 5  M⊙ and z end = 4.0), and First ( V ∼ (3 cMpc) 3, m SPH = 7.9 × 10 3  M⊙ and z end = 9.5) runs, that allow us to focus on different aspects of galaxy formation. In the PCR runs, we follow 10 PCs, each harbouring 1–4 SMBHs with ${\rm M_{\rm BH}}\ge 10^{9}~{\rm M_{\odot }}$ . One of the PC cores shows a spatially close arrangement of seven starburst galaxies with ${\rm SFR} \gtrsim 100~{\rm {\rm M_{\odot }}~{\rm yr^{-1}}}$ each, that are dust-obscured and would appear as submillimetre galaxies with flux ≳1 mJy at $1.1~ \rm mm$ in observations. The BCG runs show that the total SFRs of haloes hosting BCGs are affected by AGN feedback, but exceed $1000~{\rm {\rm M_{\odot }}~{\rm yr^{-1}}}$ at z ≲ 6. The First runs resolve mini-haloes hosting population (Pop) III stars and we show that, in PC regions, the dominant stellar population changes from Pop III to Pop II at z ≳ 20, and the first galaxies with ${\rm SFR} \gtrsim 18~{\rm {\rm M_{\odot }}~{\rm yr^{-1}}}$ form at z ∼ 10. These can be prime targets for future observations with the James Webb Space Telescope . Our simulations successfully reproduce the global star formation activities in observed PCs and suggest that PCs can kickstart cosmic reionization.